Surface Plasmon-Enhanced Nanoantenna for Localized Fluorescence - Isa Kocakarin; Korkut Yegin (International Journal of Antennas and Propagation)
Surface plasmon-enhanced gold nanoantenna structures on glass substrate are studied for increased localized electric field and fluorescence at the feed gap locations of the antennas. Dipole, Archimedean balanced spiral, and bowtie and double bowtie geometries are studied for surface plasmon effect. Different flare angles for bowtie geometries are compared to each other. Double bowtie geometry with dual polarization capability exhibited superior performance with almost 56 dB field enhancement factor. We also studied the effect of substrate thickness on electric field enhancement and we found that glass thickness plays a critical role for coherent addition of surface plasmons at the feed gap location. The surface plasmon effect is proven by considering perfect electric conductor model of gold instead of its modified Drude model.